Квадратные уравнение. решите уравнение а 9x²-4=0б 2x²=3xв 2 = 7x²+2г 2x+1 x-4=x-2x+2

квадратные уравнение. решите уравнение 

а) 9x²-4=0
б) 2x²=3x
в) 2 = 7x²+2
г) (2x+1) (x-4)=(x-2)(x+2)

  • …………………………………………
  • a)9x²-4=0
    D=0²-4*9*(-4)=-4*9*(-4)=-36*(-4)=-(-36*4)=-(-144)=144;
    X1=(√144-0)/(2*9)=12/(2*9)=12/18=0.666666666666667;
    X2=(-√144-0)/(2*9)=-12/(2*9)=-12/18=-0.666666666666667.
    б)
    2x²=3x
    ²-3х²=0
    D=(-3)²-4*2*0=9-4*2*0=9-8*0=9;
    X1=(
    √9-(-3))/(2*2)=(3-(-3))/(2*2)=(3+3)/(2*2)=6/(2*2)=6/4=1.5;
    X2=(-
    √9-(-3))/(2*2)=(-3-(-3))/(2*2)=(-3+3)/(2*2)=0/(2*2)=0/4=0.
    в)
    2 = 7x²+2
    -7х
    ²=0
    X1=√(0/7)=√0=0; 
    X2=-√(0/7)=-√0=0. 
    г)(2x+1) (x-4)=(x-2)(x+2)
          х
    ²-7х=0
      (2*X+1)*(X-4)=2*X^2-7*X-4
      (X-2)*(X+2)=X^2-4
       2*X^2-7*X-4-(X^2-4)=2*X^2-7*X-4-X^2+4
       2*X^2-X^2=1*X^2
          -4+4=0
     2*X^2-7*X-4-(X-2)*(X+2)=0
     2*X^2-7*X-4-(X^2-4)=0
     2*X^2-7*X-4-X^2+4=0
     X^2-7*X-4+4=0
          X^2-7*X=0
    D=(-7)^2-4*1*0=49-4*0=49;
    X1=(√49-(-7))/(2*1)=(7-(-7))/2=(7+7)/2=14/2=7;
    X2=(-49-(-7))/(2*1)=(-7-(-7))/2=(-7+7)/2=0/2=0.




Внимание, только СЕГОДНЯ!